Can Industrial Relocation Reduce Air Pollution? Evidence From a Quasi-Natural Experiment in China - Ge, Tao; Lv, Xuchen; Ma, Li; Shen, Xiaoyan (Frontiers in Environmental Science, 2022)
To reduce the increasingly severe air pollution caused by rapid industrialization, China has introduced a National Industrial Relocation Demonstration Zones (NIRDZs) policy. This paper takes the NIRDZs as a quasi-natural experiment and employs the difference-in-differences (DID) method to test the effects of industrial relocation on air pollution based on panel data of 285 prefecture-level cities from 2003 to 2018. Results show that the NIRDZs have an inhibitory effect on SO2 emissions, although their local effect is significant in the first five years and their spillover effect only occurs within 50-100 km. Mechanism analysis reveals that the NIRDZs reduce air emissions by rationalizing and upgrading the industrial structure. Additionally, further discussions suggest that cities with moderate administrative areas and abundant natural resources should be prioritized as pilot cities, and industries including nonferrous metals, steel, automotive, new energy, new materials, and producer services should be designated as priority industries.